The Sanctions-Perceptions Link in a Model of School-based Deterrence - Apel, Robert (Journal of quantitative criminology, 2009)
This paper reports a study examining associations between objective indicators of the level of discipline within schools and students’ perceptions of the strictness of discipline. Data were analyzed from the National Education Longitudinal Survey (NELS), a nationally representative panel study of eighth grade students attending public and private schools in 1988. We find evidence for an association between objective and perceived risk of discipline in models that examine the covariation of these two constructs at several cross sections, and in models of change in perceptions as a function of change in school sanctioning climate. Moreover, these associations were strongest in small and less disordered schools.